2020
DOI: 10.3390/jcm9092684
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dupilumab on Different Phenotypes of Atopic Dermatitis: One-Year Experience of 221 Patients

Abstract: Background: The clinical features of adult-onset atopic dermatitis (AD) are heterogeneous and the diagnosis can be a challenge. A new biologic drug (dupilumab) has been approved for moderate to severe AD in adult patients. The efficacy and safety have been demonstrated in clinical trials, but these studies do not reflect conditions in daily practice and do not consider the different clinical manifestations of AD. Objectives: Analyzing the dupilumab activity in a real-world setting and comparing its efficacy on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 21 publications
(22 reference statements)
5
54
0
2
Order By: Relevance
“…8 Although TEA of concomitant therapeutic agents and classification of PN was not evaluated, a group from Italy also reported that prurigo may be one of the slow-responding AD phenotypes. 29 In EASI-75 assessment, the prurigo group in the present study appeared to show even slower improvement (8.3% at intractable prurigo in patients with AD via itch soothing through the multimodal mechanisms mentioned above as well as through attenuating the Th2 immunity that is vital in the etiology of AD.…”
Section: Discussionmentioning
confidence: 47%
“…8 Although TEA of concomitant therapeutic agents and classification of PN was not evaluated, a group from Italy also reported that prurigo may be one of the slow-responding AD phenotypes. 29 In EASI-75 assessment, the prurigo group in the present study appeared to show even slower improvement (8.3% at intractable prurigo in patients with AD via itch soothing through the multimodal mechanisms mentioned above as well as through attenuating the Th2 immunity that is vital in the etiology of AD.…”
Section: Discussionmentioning
confidence: 47%
“…Dupilumab shows clear and maintained effectiveness over a 76week treatment duration, decreased skin lesions and pruritus, and increased quality of life reported by Deleuran, et al [27]. Tavecchio, et al reported a possible change in AD classical and erythroderma phenotypes after 16 weeks of dupilumab therapy (p<0.0001) and progressed until week 52 [21].…”
Section: Classic Erythroderma and Pruritismentioning
confidence: 80%
“…Dupilumab shows a substantial increase in the disease after 16 weeks of therapy, as shown by a decline in EASI and DLQI ratings. Similarly, Tavecchio, et al reported a significant increase in nummular eczema [21], generalized inflammatory eczema and generalized phenotypic lichenoid pattern eczema after 16 weeks of therapy with dupilumab (p<0.0001) and continued until week 52. In addition, the authors stated that decreases in EASI were slower in nummular eczema phenotypes than in other phenotypes, suggesting that treatment should not be halted until an adequate therapeutic result has been obtained.…”
Section: Nummular Eczema and Generalized Eczemamentioning
confidence: 84%
See 2 more Smart Citations